AI-Enabled Digital Experience Design for Enterprise Applications and Platforms: Advancing Inclusion, Equity, and Societal Participation - Muthu Saravanan Ramachandran (International Journal of Intelligent Systems and Applications in Engineering, 2026)
Enterprise digital platforms have become the foundational infrastructure through which citizens access healthcare, government services, education, and financial systems, yet across these critical domains, complex interfaces routinely exclude the populations most dependent on them through inaccessible design, cognitively demanding workflows, and content calibrated to narrow assumptions about user capability. People with disabilities, limited digital literacy, non-native language backgrounds, aging-related cognitive changes, and low-bandwidth connectivity constraints face systemic obstacles and. these barriers deprive them of access to healthcare, financial stability, and civic engagement services. The latter failures are not design oversights within their particularity; they are indicative of the structural inability of the traditional experience design methods to deal with population-level diversity at enterprise scale. The digital experience design based on AI can provide a radically different and scalable answer by augmenting human design knowledge with automated behavioral pattern recognition, perpetual accessibility testing, plain language testing, and intelligent quick prototyping. Such abilities turn the inclusive design into a dream and a structured and operationally viable practice in healthcare access, civic participation, educational equity, and financial inclusion. Ongoing automated accessibility checking during platform development minimizes WCAG compliance violations in ways that human review alone cannot achieve. Additionally, population-stratified behavioral analysis reveals failure patterns that aggregate usability metrics obscure and that small-scale testing cannot uncover. Platforms redesigned through AI-supported inclusive design show significantly higher task completion among underserved groups and also demonstrate decreased citizen support escalations, enhanced patient portal engagement, and increased financial service adoption among historically excluded populations. The major point of view that this body of evidence advocates is that AI is not a replacement for human design skills, but it enhances the potential of empathy-driven, morally based designers to reach the entire gamut of human diversity that digitally dependent societies need.